2018
DOI: 10.1021/acsanm.8b01555
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Strain Concentration on a Two-Dimensional Nanobridge within a Large Suspended Bilayer Graphene for Molecular Mass Detection

Abstract: The recent emergence of strain gradient engineering directly affects the nanomechanics, optoelectronics and thermal transport fields in 2D materials. More specifically, large suspended graphene under very high stress represents the quintessence for nanomechanical mass detection through unique molecular reactions. Different techniques have been used to induce strain in 2D materials, for instance by applying tip indentation, pressure or substrate bending on a graphene membrane. Nevertheless, an efficient way to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Furthermore, scanning thermal microscopy measurements have demonstrated that graphene can also act as a thermally conducting coating on a variety of substrates such as SiO 2 , Al 2 O 3 , and poly­(ethylene terephthalate) . Graphene also has great potential for molecular mass detection using nanobridges of bilayer graphene, as well as for proton-selective transmission by sandwiching graphene between proton-exchange membranes . On the other hand, photodetectors made of graphene oxide–semiconductor junctions display high responsivities …”
Section: Organic 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, scanning thermal microscopy measurements have demonstrated that graphene can also act as a thermally conducting coating on a variety of substrates such as SiO 2 , Al 2 O 3 , and poly­(ethylene terephthalate) . Graphene also has great potential for molecular mass detection using nanobridges of bilayer graphene, as well as for proton-selective transmission by sandwiching graphene between proton-exchange membranes . On the other hand, photodetectors made of graphene oxide–semiconductor junctions display high responsivities …”
Section: Organic 2d Materialsmentioning
confidence: 99%
“…The structures highlighted above were adapted from the publications in this virtual issue as follows: SnS, 17 GeS, 18 BP, 20 h-BN, 27 MoO 3 , 24 CPs, 38 HOFs, 40 MOCHAs, 41 MXenes, 44 and heterostructures 2D/2D, 49 1D/2D, 55 coating on a variety of substrates such as SiO 2 , Al 2 O 3 , and poly(ethylene terephthalate). 32 Graphene also has great potential for molecular mass detection using nanobridges of bilayer graphene, 33 as well as for proton-selective transmission by sandwiching graphene between proton-exchange membranes. 34 On the other hand, photodetectors made of graphene oxide−semiconductor junctions display high responsivities.…”
Section: Organic 2d Materialsmentioning
confidence: 99%
“…The misfit strain in a heterostructure can be controlled in various ways, e.g. by appropriately choosing the substrate [29] and the structural design [30], or by photoelectrochemical etching process [31]. The misfit strain directly affects the physical and mechanical properties of a vdW heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…As a characteristic feature for the van der Waals heterostructure, there is an inevitable misfit strain between the constituting atomic layers, which can be caused by various reasons including the different lattice constants for these different atomic layers [21][22][23]. The strain in the atomic layers can be manipulated through various experimental techniques, including the substrate [24], the photoelectrochemical etching process [25], the structural design [26], and etc. Experiments have demonstrated the effect of the relative sliding of two graphene layers on the electrical properties of bilayer graphene [27,28].…”
Section: Introductionmentioning
confidence: 99%